Zero-spontaneous-explosion fireproof power generation glass

By using a combination of a modified boron trioxide heat-dip coating layer and a cadmium telluride absorbing layer in photovoltaic power glass, the fire hazards and self-destruction risks of traditional photovoltaic power glass are solved, and higher temperature resistance and fire resistance and system stability are achieved.

CN119638209APending Publication Date: 2025-03-18BEIJING HAIYANG SHUNDA GLASS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411928006.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional photovoltaic power glass has fire hazards and glass self-destruction risks, resulting in equipment damage and power fires.

Method used

The zero-self-detonation fire-proof power generation glass consisting of a glass substrate, an absorption layer and a modified diboron trioxide heat-diplate film layer is used to form a multiple fire-proof mechanism to improve the temperature and fire resistance of the glass through the synergy between modified diboron trioxide and P,P-diphenylhydrazine phosphate.

Benefits of technology

Effectively isolate oxygen, slow down heat penetration, improve the temperature resistance and fire resistance of fire-resistant power generation glass, reduce fire hazards and glass self-destruction risks, and ensure the long-term and stable operation of the photovoltaic power generation system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of power generation glass, and provides zero-spontaneous-explosion fireproof power generation glass which sequentially comprises a glass substrate and an absorption layer from bottom to top. The surface of the glass substrate further comprises a heat insulation coating layer, a solid target material of the heat insulation coating layer is modified diboron trioxide, the modified diboron trioxide is obtained by modifying diboron trioxide through a modifier, and the modifier comprises titanium salt. According to the technical scheme, the problem that fireproof power generation glass is low in temperature resistance and fireproof performance in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of power generation glass, and in particular to zero self-explosion fireproof power generation glass. Background Art

[0002] As the global demand for clean energy grows, photovoltaic power generation, as a sustainable and pollution-free way to obtain energy, occupies an increasingly important position in the energy field. In photovoltaic power generation systems, power generation glass, with its unique advantages, not only has the lighting, wind and rain protection functions of traditional architectural glass, but also can efficiently convert solar energy into electrical energy. It is widely used in various building curtain walls, photovoltaic roofs and other scenes, achieving the dual benefits of building energy conservation and power generation.

[0003] However, traditional photovoltaic power generation technology has drawbacks that cannot be ignored, and fire hazards are one of them. Once an electric fire occurs in a photovoltaic power generation facility, the fire often spreads rapidly. On the one hand, the photovoltaic power generation system involves a large number of electrical lines, inverters, junction boxes and other equipment. Electrical problems such as line short circuit, overload, poor contact and electrical equipment failure can easily cause electric sparks, instantly igniting surrounding flammable materials, such as photovoltaic module packaging materials, protective coatings of mounting brackets, etc. In addition, photovoltaic arrays are usually laid over a large area and interconnected, which builds a convenient "channel" for the spread of fire and can cover a large area in a short time. On the other hand, when a fire occurs, many photovoltaic modules and auxiliary electrical equipment will release a large amount of toxic and harmful substances during the combustion process. Common ones include acidic gases such as hydrogen chloride and hydrogen fluoride, as well as organic pollutants such as polycyclic aromatic hydrocarbons and dioxins. These toxic substances diffused in the air not only cause serious obstacles to on-site fire fighting and rescue work, threatening the lives of rescuers, but also have long-term negative impacts on the surrounding environment and ecology, polluting soil, water sources and air, and endangering the health of residents.

[0004] Among the many components of photovoltaic power generation systems, the glass itself also has the potential risk of self-explosion. Self-explosion refers to the phenomenon that the glass itself suddenly breaks and is damaged without strong external mechanical impact or other strong forces. The reasons for its occurrence are quite complicated. First, it is caused by internal defects. During the manufacturing process, the original glass may be mixed with impurity particles, such as iron filings in quartz sand, incompletely melted stones, etc. These impurities have a great difference in thermal expansion coefficient with the glass matrix. When the temperature changes, stress concentration is generated due to inconsistent expansion or contraction. When the stress exceeds the limit of the glass, it will cause self-explosion; second, the tempering process defects. If the heating is uneven and the cooling rate is improperly controlled during the tempering process, it will cause uneven prestress distribution inside the glass. During use, it will be affected by environmental factors such as external temperature and wind pressure. The stress imbalance causes the glass to explode. Once the power generation glass explodes, it will not only directly lead to the loss of the power generation function of the glass, but the scattered fragments may also damage the surrounding equipment and the building structure. More seriously, the broken glass surface is prone to dust accumulation and water ingress in outdoor environments, causing internal circuit short circuits, becoming one of the factors that induce power fires. Therefore, it is necessary to develop a zero self-explosion fireproof power generation glass. Summary of the invention

[0005] The present invention proposes zero self-explosion fireproof power generation glass, which solves the problem of low heat resistance and fireproof performance of fireproof power generation glass in the related art.

[0006] The technical solution of the present invention is as follows: The present invention proposes a zero self-explosion fireproof power generation glass, which includes a glass substrate and an absorption layer from bottom to top; the surface of the glass substrate also includes a thermal insulation coating layer, and the solid target material of the thermal insulation coating layer is modified boron trioxide, and the modified boron trioxide is obtained by modifying boron trioxide with a modifier, and the modifier includes titanium salt.

[0007] As a further technical solution, the glass substrate is borosilicate glass.

[0008] As a further technical solution, the absorption layer is a cadmium telluride film.

[0009] As a further technical solution, the preparation method of the modified boron trioxide comprises the following steps: boron trioxide and titanium salt are co-precipitated and modified to obtain modified boron trioxide.

[0010] As a further technical solution, the titanium salt includes one or both of titanium tetrachloride and titanium tetrafluoride.

[0011] As a further technical solution, the preparation method of the modified boron trioxide comprises the following steps: S1. Dispersing boron trioxide in solution I, stirring, filtering and drying to obtain activated boron trioxide; S2, dispersing the activated boron trioxide in solution II to obtain a solution containing boron trioxide; S3, dispersing the titanium salt in solution III to obtain a solution containing the titanium salt; S4. Adding the solution containing titanium salt into the solution containing boron trioxide, after co-precipitation, filtering, drying and calcining, the modified boron trioxide is obtained.

[0012] As a further technical solution, the mass ratio of the titanium salt to the boron trioxide is 9-10:100.

[0013] As a further technical solution, the solution I in S1 is a hydrochloric acid solution with a concentration of 0.1 mol / L, and the mass ratio of the solution I to the boron trioxide is 10:1.

[0014] As a further technical solution, the stirring time in S1 is 1 to 2 hours.

[0015] As a further technical solution, the solution II in S2 is an octanol solution, and the mass ratio of the solution II to the boron trioxide is 10:1.

[0016] As a further technical solution, the solution III in S3 is a hydrochloric acid solution, and the mass ratio of the solution III to the titanium salt is 10:1.

[0017] As a further technical solution, the co-precipitation time in S4 is 10-20 minutes, the co-precipitation temperature is 60-80° C., and the pH value is less than 1 during the co-precipitation process.

[0018] As a further technical solution, the calcination temperature in S4 is 400-450° C., and the calcination time is 30-40 min.

[0019] As a further technical solution, the modifier also includes P,P-diphenylhydrazine phosphate.

[0020] In the present invention, on the basis of titanium salt-modified boron trioxide, P,P-diphenyl hydrazine phosphate is used to perform secondary modification on titanium salt-modified boron trioxide, and the synergistic effect of the two modifications is exerted to form a multiple fire protection mechanism, effectively isolate oxygen, slow down heat penetration, and further improve the heat resistance and fire resistance of the fireproof power generation glass.

[0021] As a further technical solution, the preparation method of the modified boron trioxide includes the following steps: dispersing P,P-diphenylhydrazine phosphate in solution IV, adding boron trioxide modified by titanium salt, filtering and drying after modification to obtain modified boron trioxide.

[0022] As a further technical solution, the mass ratio of the P,P-diphenylhydrazine phosphate to the boron trioxide modified by the titanium salt is 6-7:50.

[0023] As a further technical solution, the solution IV is anhydrous ethanol, and the mass ratio of the solution IV to the boron trioxide modified with titanium salt is 10:1.

[0024] As a further technical solution, the modification temperature is 40° C. and the modification time is 4 hours.

[0025] The present invention also proposes a method for preparing zero self-explosion fireproof power generation glass, comprising the following steps: assembling a glass substrate and an absorption layer in order from bottom to top, sputtering a solid target material on the surface of the glass substrate to form a thermal insulation coating layer, thereby obtaining zero self-explosion fireproof power generation glass.

[0026] As a further technical solution, the vacuum degree of the sputtering vacuum environment is 6×10 -4 Pa.

[0027] The working principle and beneficial effects of the present invention are: In the present invention, the fire prevention function and the power generation function are organically combined on the power generation glass, giving the power generation glass a reliable fire prevention ability, reducing equipment damage and shutdown maintenance frequency caused by fire hazards and glass self-explosion, ensuring the long-term stable operation of the photovoltaic power generation system, continuously and efficiently producing electricity, and improving the overall economic benefits of the photovoltaic power generation project. In the present invention, boron trioxide is modified by titanium salt to prepare a thermal insulation coating layer. By constructing an efficient thermal insulation network on the glass surface, it effectively prevents flame heat from penetrating, thereby improving the temperature resistance and fire resistance of the fireproof power generation glass. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In the following examples and comparative examples: Glass substrate: high borosilicate fireproof glass, thickness 8mm; Absorption layer: cadmium telluride film, thickness 0.32μm; Thermal insulation coating layer: thickness is 120nm; Boron trioxide: The average particle size is 100nm.

[0030] Example 1 The preparation method of modified boron trioxide comprises the following steps: S1. Weigh 10 parts of boron trioxide and add them to 100 parts of 0.1 mol / L hydrochloric acid solution. Stir for 1 hour, filter and dry to obtain activated boron trioxide. S2, dispersing the activated boron trioxide in 100 parts of n-octanol solution to obtain a solution containing boron trioxide; S3, dispersing 0.9 parts of titanium tetrachloride in 9 parts of hydrochloric acid solution to obtain a mixed solution containing titanium salt; S4, adding a solution containing titanium salt to a solution containing boron trioxide to obtain a modified solution, controlling the pH of the modified solution to be less than 1, heating the solution to 60° C., modifying the solution for 20 minutes, filtering, drying, and calcining the solution at 400° C. for 40 minutes to obtain modified boron trioxide, i.e., a solid target material; The preparation method of zero self-explosion fireproof power generation glass comprises the following steps: assembling a glass substrate and an absorption layer in order from bottom to top, sending them into a vacuum magnetron sputtering device, and placing them in a vacuum environment with a vacuum degree of 6×10 -4 Pa, a solid target material is sputtered on the surface of the outer glass substrate to form a heat-insulating coating layer, thereby obtaining a zero self-explosion fire-proof power generation glass, wherein the solid target material is the modified boron trioxide obtained by the above preparation method.

[0031] Example 2 The preparation method of modified boron trioxide comprises the following steps: S1. Weigh 10 parts of boron trioxide and add them to 100 parts of 0.1 mol / L hydrochloric acid solution. Stir for 1.5 hours, filter and dry to obtain activated boron trioxide. S2, dispersing the activated boron trioxide in 100 parts of n-octanol solution to obtain a solution containing boron trioxide; S3, dispersing 0.9 parts of titanium tetrachloride in 9 parts of hydrochloric acid solution to obtain a mixed solution containing titanium salt; S4, adding a solution containing titanium salt to a solution containing boron trioxide to obtain a modified solution, controlling the pH of the modified solution to be less than 1, heating the solution to 70° C., modifying the solution for 15 minutes, filtering and drying the solution, and calcining the solution at 420° C. for 35 minutes to obtain modified boron trioxide, i.e., a solid target material; The preparation method of zero self-explosion fireproof power generation glass comprises the following steps: assembling a glass substrate and an absorption layer in order from bottom to top, sending them into a vacuum magnetron sputtering device, and placing them in a vacuum environment with a vacuum degree of 6×10 -4 Pa, a solid target material is sputtered on the surface of the outer glass substrate to form a heat-insulating coating layer, thereby obtaining a zero self-explosion fire-proof power generation glass, wherein the solid target material is the modified boron trioxide obtained by the above preparation method.

[0032] Example 3 The preparation method of modified boron trioxide comprises the following steps: S1. Weigh 10 parts of boron trioxide and add them to 100 parts of 0.1 mol / L hydrochloric acid solution. Stir for 2 hours, filter and dry to obtain activated boron trioxide. S2, dispersing the activated boron trioxide in 100 parts of n-octanol solution to obtain a solution containing boron trioxide; S3, dispersing 0.9 parts of titanium tetrachloride in 9 parts of hydrochloric acid solution to obtain a mixed solution containing titanium salt; S4, adding a solution containing titanium salt to a solution containing boron trioxide to obtain a modified solution, controlling the pH of the modified solution to be less than 1, heating the solution to 80° C., modifying the solution for 10 minutes, filtering and drying the solution, and calcining the solution at 450° C. for 30 minutes to obtain modified boron trioxide, i.e., a solid target material; The preparation method of zero self-explosion fireproof power generation glass comprises the following steps: assembling a glass substrate and an absorption layer in order from bottom to top, sending them into a vacuum magnetron sputtering device, and placing them in a vacuum environment with a vacuum degree of 6×10 -4 Pa, a solid target material is sputtered on the surface of the outer glass substrate to form a heat-insulating coating layer, thereby obtaining a zero self-explosion fire-proof power generation glass, wherein the solid target material is the modified boron trioxide obtained by the above preparation method.

[0033] Example 4 Compared with Example 1, the difference of Example 4 is that the added amount of boron trioxide is 1 part.

[0034] Example 5 The preparation method of modified boron trioxide comprises the following steps: dispersing 1.2 parts of P,P-diphenylphosphhydrazine in 100 parts of ethanol, adding 10 parts of boron trioxide, heating to 40°C for modification for 4 hours, filtering and drying to obtain modified boron trioxide.

[0035] Compared with Example 4, the difference of Example 5 is that the solid target material is replaced by modified boron trioxide obtained by the above preparation method.

[0036] Example 6 Compared with Example 5, the difference of Example 6 is that the boron trioxide is replaced by an equal amount of the modified boron trioxide prepared in Example 4.

[0037] Example 7 Compared with Example 6, the difference in Example 7 is that the amount of P,P-diphenylphosphhydrazine added is 1.4 parts.

[0038] Comparative Example 1 Compared with Example 1, Comparative Example 1 is different in that a solid target material is not sputtered on the surface of the outer glass substrate to form a thermal insulation coating layer.

[0039] Comparative Example 2 Compared with Example 1, the difference in Comparative Example 2 is that the solid target material is boron trioxide.

[0040] The zero self-explosion fireproof power generation glass obtained in Examples 1 to 7 and Comparative Examples 1 to 2 was tested according to the following method: 1. Fire integrity time: According to the test method specified in GB 15763.1-2009 "Safety glass for building Part 1: Fire-resistant glass", the fire integrity time of the test sample is tested.

[0041] 2. Fire resistance limit: Test the fire resistance limit of the sample according to the test method specified in GB 15763.1-2009 "Safety glass for building Part 1: Fire-resistant glass".

[0042] The test results are shown in the following table: Table 1 Performance test results of zero self-explosion fireproof power generation glass prepared in Examples 1 to 7 and Comparative Examples 1 to 2

[0043] Compared with Comparative Examples 1 and 2, Example 1 adds modified boron trioxide obtained by modification with titanium salt as a solid target material, and sputters the solid target material on the surface of the outer glass substrate to form a thermal insulation coating layer. As a result, the fire resistance integrity and fire resistance limit of Example 1 are better than those of Comparative Examples 1 and 2, indicating that when modified boron trioxide obtained by modification with titanium salt is added as a solid target material, the heat resistance and fire resistance of the fire-proof power generation glass can be improved.

[0044] Compared with Examples 4 and 5, Examples 6 and 7 use titanium salt and P,P-diphenylhydrazine phosphate to modify boron trioxide, prepare modified boron trioxide as a solid target, and sputter the solid target on the surface of the outer glass substrate to form an insulating coating layer. As a result, the fire resistance integrity and fire resistance limit of Examples 6 and 7 are better than those of Examples 4 and 5, indicating that titanium salt and P,P-diphenylhydrazine phosphate have a synergistic effect, which can further improve the heat resistance and fire resistance of fire-resistant power generation glass.

[0045] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. Zero self-explosion fireproof power generation glass, characterized by: From bottom to top, it includes a glass substrate and an absorption layer; the surface of the glass substrate also includes a thermal insulation coating layer, the solid target material of the thermal insulation coating layer is modified boron trioxide, and the modified boron trioxide is obtained by modifying boron trioxide with a modifier, and the modifier includes titanium salt.

2. The zero self-explosion fireproof power generation glass according to claim 1, characterized in that: The glass substrate is borosilicate glass.

3. The zero self-explosion fireproof power generation glass according to claim 1, characterized in that: The absorption layer is a cadmium telluride thin film.

4. The zero self-explosion fireproof power generation glass according to claim 1, characterized in that: The preparation method of modified diboron trioxide comprises the following steps: diboron trioxide and titanium salt are co-precipitated and modified to obtain modified diboron trioxide.

5. The zero self-explosion fireproof power generation glass according to claim 1, characterized in that: The titanium salt includes one or both of titanium tetrachloride and titanium tetrafluoride.

6. The zero self-explosion fireproof power generation glass according to claim 4, characterized in that: The preparation method of the modified boron trioxide comprises the following steps: S1. Dispersing boron trioxide in solution I, stirring, filtering and drying to obtain activated boron trioxide; S2, dispersing the activated boron trioxide in solution II to obtain a solution containing boron trioxide; S3, dispersing the titanium salt in solution III to obtain a solution containing the titanium salt; S4. Adding the solution containing titanium salt into the solution containing boron trioxide, after co-precipitation, filtering, drying and calcining, the modified boron trioxide is obtained.

7. The zero self-explosion fireproof power generation glass according to claim 1, characterized in that: The mass ratio of the titanium salt to the boron trioxide is 9-10:

100.

8. The zero self-explosion fireproof power generation glass according to claim 1, characterized in that: The modifier also includes P,P-diphenylhydrazine phosphate.

9. The zero self-explosion fireproof power generation glass according to claim 8, characterized in that: The preparation method of modified boron trioxide comprises the following steps: dispersing P,P-diphenyl hydrazine phosphate in solution IV, adding boron trioxide modified by titanium salt, filtering and drying after modification to obtain modified boron trioxide.

10. The zero self-explosion fireproof power generation glass according to claim 9, characterized in that: The mass ratio of the P,P-diphenyl hydrazine phosphate to the boron trioxide modified by the titanium salt is 6-7:50.

Citation Information

Patent Citations

  • Titanium diboride ceramic powder low-temperature solid-phase synthesizing method

    CN103253678A

  • Protective coatings for photovoltaic cells

    CN104205355A

  • Foam glass ceramic composite building thermal insulation material and preparation method thereof

    CN109399942A

  • Boric oxide and titanium dioxide composite nanomaterial and preparing method thereof

    CN110292919A

  • Bulletproof and fireproof glass capable of generating electricity and preparation process thereof

    CN110712406A